EXAMINING MEANING IN LIFE AMONG PATIENTS WITH THALASSEMIA: A CROSS SECTIONAL STUDY - Khan, Tayyaba; Rauf, Khalida (Pakistan Journal of Clinical Psychology, 2025)
Objectives: The study was conducted with the aim of examining meaning in life among patients with thalassemia, the knowledge of which is essential in developing more suitable clinical, counseling, and social support programs to improve treatment outcomes of these patients. Design of the Study: A comparative research design Place and Duration of Study: Different Universities of Karachi from January 2022-January 2023 Sample and method: The study sample consisted of 45 thalassemia patients (ages 11 to 50 years) who were selected randomly, who completed the Meaning in life Questionnaire (Steger et al., 2006) comprising 10 items to determine the presence and search for meaning. Results and Conclusion: Results showed that minor thalassemia patients had higher meaning in life than major thalassemia patients (P<.05). Results regarding gender and age were inconclusive. It may be concluded that higher meanings in life in patients with Thalassemia minor not only reduces distress but also contribute in better adjustment with the disease.